Detection of recurrent thyroid cancer: MR versus thallium-201 scintigraphy. - Ohnishi, T; Noguchi, S; Murakami, N; Jinnouchi, S; Hoshi, H; Futami, S; Watanabe, K (American Journal of Neuroradiology, 1993)
PURPOSE To compare MR with thallium-201 scintigraphy in the follow-up of patients who have undergone thyroidectomy and modified radical neck dissection for differentiated thyroid cancer.METHODS Both MR imaging and 201Tl scintigraphy were performed in 39 patients after surgery for differentiated thyroid cancer. Ten patients did not have recurrence; 29 patients had 51 recurrent tumors in the neck and mediastinum.RESULTS Among 51 tumor sites, 39 sites of recurrence were detected by MR and 24 were detected by 201Tl scintigraphy. The true-positive rate, false-negative rate, true-negative rate, and false-positive rate in detecting recurrent thyroid cancer were 76.5, 23.5, 100, and 0%, respectively, for MR and 47.1, 52.9, 100, and 0%, respectively, for 201Tl scintigraphy. MR was more sensitive than 201Tl scintigraphy in detecting recurrent tumors (especially small metastatic nodes). On T2-weighted MR images, recurrent tumor was characterized by high signal intensity. Scarring in the postoperative thyroid bed was characterized by low signal intensity on both T1- and T2-weighted images. Abnormal accumulation of 201Tl in the postoperative thyroid bed was not observed.CONCLUSIONS Although both MR images and 201Tl scintigraphy were effective in distinguishing recurrent tumor from postoperative fibrous tissue, MR images were more sensitive than 201Tl scintigraphy in detecting recurrent tumors. These results suggest that MR imaging is more useful than 201Tl scintigraphy in the follow-up evaluation of patients after neck surgery for differentiated thyroid cancer.